MS4A6A is a new prognostic biomarker produced by macrophages in glioma patients - Zhang, Chunyu; Liu, Haitao; Tan, Yinqiu; Xu, Yang; Li, Yuntao; Tong, Shiao; Qiu, Sheng; Chen, Qianxue; Su, Zhongzhou; Tian, Daofeng; Zhou, Wei; Zhong, Chunlong (Frontiers in Immunology, 2022)
MS4A6A has been recognized to be associated with aging and onset of neurodegenerative disease. However, the mechanisms of MS4A6A in glioma biology and prognosis are ill-defined. Here, we found that MS4A6A was upregulated in glioma tissues, resulting in unfavorable clinical outcome and poor response to adjuvant chemotherapy. Multivariate Cox regression analysis suggested MS4A6A expression could act as a strong and independent predictor for glioma outcomes (CGGA1: HR: 1.765, P < 0.001; CGGA2: HR: 2.626, P < 0.001; TCGA: HR: 1.415, P < 0.001; Rembrant: HR: 1.809, P < 0.001; Gravendeel: HR: 1.613, P < 0.001). The protein-protein interaction (PPI) network revealed MS4A6A might co-express with CD68 and CD163, macrophage-specific signatures. Enrichment analysis demonstrated innate immune response, and inflammatory response were remarkably enriched in high MS4A6A expression group. Meanwhile, single cell RNA sequencing (scRNA-seq) analysis was conducted and uncovered MS4A6A had the distinctive expression features in macrophages in glioma immune microenvironment (GIME). Immunofluorescence staining confirmed the co-location of CD68/MS4A6A and CD163/MS4A6A in macrophages. Correlation analysis revealed MS4A6A expression was positively related to tumor mutation burden (TMB) of glioma, displaying the highly potentiality of MS4A6A applied to evaluate the responsiveness to immunotherapy. Altogether, our research indicated that MS4A6A upregulation could be used as a promising and effective indicator for adjuvant therapy and prognosis assessment.